(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The aim of present study was to Impact of Personal Stress, Locality and Gender among Senior Secondary School Teachers on Burnout. In this descriptive study, organizational commitment, occupational self-efficacy and personal stress have been treated as independent variables whereas burnout has been treated as dependent variable. The sample of 400 senior secondary school teachers was selected by a multi-stage random sampling technique. Teachers’ Burnout Scale (TBS-G M R S) by Gupta and Rani, Organizational Commitment scale by Hyde and Roy (2006), Occupational Self-efficacy Scale by Pethe et al. (1999) and Personal Stress Source Inventory by Singh, Singh and Singh (2011) were used to collect the data. Pearson’s coefficients of correlation (r) and stepwise multiple regression were employed as statistical techniques in the present study. It was concluded that the variable personal stress was found to be the strongest predictor of Psychological Well-Being in comparison to organizational commitment and occupational self-efficacy.